Spontaneous regression of large-sized lumbar facet synovial cysts: two case reports and literature review - Hong Jin Kim; Jong-Hyun Ko; Dong-Gune Chang (BMC Musculoskeletal Disorders)
Abstract Background Lumbar facet synovial cysts (LFSCs) are an uncommon degenerative lesion in the lumbar spine, but treatment remains controversial. We report two rare cases of spontaneous regression of large-sized LFSCs. Case presentation A 68-year-old male visited our outpatient clinic with a complaint of lower back pain and right lower extremity radiculopathy beginning approximately two weeks prior. Computed tomography of the spine showed facet arthrosis, and magnetic resonance imaging (MRI) of the spine revealed a large, oval cystic-mass-like lesion at the L5–S1 level. After conservative treatment for one year, the patient’s symptoms had completely resolved, and a follow-up MRI showed spontaneous regression of the large LFSC. A 69-year-old female with a complaint of radiating pain on left lower extremity and intermittent claudication that had aggravated about 2 months ago also showed a 1.5 × 1.2 × 1.7 cm oval cystic mass involving left L5, S1 nerve roots at L5–S1 level from the MRI. After conservative treatment for three months, a follow-up MRI also showed spontaneous resolution of the large LFSC. Conclusions The large-sized LFSCs spontaneously regressed without any surgical intervention. If symptoms can be controlled, conservative treatment should be considered for first-line treatment despite a mismatch between radiological and clinical findings. Careful clinical judgments are essential to prevent unnecessary surgery.